Eliciting Mathematical Thinking of Students through Realistic Mathematics Eucation - Lathiful Anwar; I Ketut Budayasa; Siti Maghfirotun Amin; Dede de Haan (Journal on Mathematics Education, 2012)
This paper focuses on an implementation a sequence of instructional activities about addition of fractions  that has been developed and implemented in grade four of primary school in Surabaya, Indonesia. The theory of Realistic Mathematics Education (RME) has been applied in  the  sequence, which aims to assist low attaining learners in supporting students’ thinking in the addition of fractions. Based on the premise that eliciting and addressing learners’ alternative conceptions in mathematics is beneficial in  assisting them to improve their understanding, the paper seeks to explore the role that RME plays pertaining to this particular supposition. The paper presents and discusses examples of learners’ responses to contextual problems given to them during the course of the instructional activities. Keywords: Realistic Mathematics Education, mathematical thinking, a sequence of instructional activities DOI: http://dx.doi.org/10.22342/jme.3.1.620.55-70